Observational Study of Classroom Discourse during Online Literature Circles - Aprillia, Astri (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
Online literature circles have attracted many English teachers to be used in reading classes. This research aimed to describe the interactions of online literature circles with EFL university students. The participants in this research are the students from critical reading and literacy class in one of the Islamic universities in Yogyakarta. The data were collected through the classroom observational method which the transcription data obtained from the discussion of each group at the zoom meeting. This research used the instruments adapted from Daniel (2022) about the roles of literature circles and the interactions from Guiller, Durndell, and Ross (2007) to analyze the group discussion. The finding of this research shows the students were engaged in online literature circles. Each group performs interactive discussions. Furthermore, each group member plays their role in accordance with the task description. Therefore, in this Covid-19 era, online literature circles are good to do in online classes. In addition, the lecturers are able to join the group discussion, and the presence of lecturers will provide motivation where the class will be more critical.